The Effect of Giving Virgin Coconut Oil (VCO) to Changes in Lauric Acid Levels in Breast Milk - Ismul Sadly Putra; Joserizal Serudji (Universitas Andalas, 2021)
Breastmilk (ASI) is the best food produced by the breast glands, containing all the nutritional elements needed by infants aged 0-6 months. Apart from nutrients, breast milk also has other non-nutritional components that act as immune factors for babies. Babies who are not exclusively breastfed will be more susceptible to chronic diseases, such as heart disease, hypertension, and diabetes as adults and can suffer from malnutrition and obesity. Dietary intake significantly affects milk production. The mother's diet can affect the composition of her milk through several metabolic pathways, especially the concentration of fatty acids and vitamins that are soluble in fat and water, including vitamins A, C, B6, and B12. Lauric acid contained in breast milk can help your minor fight infection and increase immunity to protect from various diseases. Not only for the baby, but virgin coconut oil is also starting to be commonly used by dieters. Virgin coconut oil contains lauric acid CH3 (CH2) 10COOH 50% and caprylic acid CH3 (CH2) 6COOH 7%. Both of these acids are medium-chain saturated fatty acids that are quickly metabolized and have anti-microbial properties. The benefits of virgin coconut oil (VCO) are that it is beneficial for the health of the body, including being antibacterial, antiviral, anti-fungal, and natural anti-protozoa; helps relieve symptoms and reduces health risks associated with diabetes, helps protect against osteoporosis, helps prevent high blood pressure, helps prevent liver disease, keeps the heart and blood vessels healthy, helps prevent cancer, helps you lose weight, maintain stamina, maintain healthy skin and hair.Keywords: Breastmilk, Lauric Acid, VCO